CONDITIONAL CLAUSES AND THEIR STRUCTURES AND METHODS OF USE - Toshtemirova Shaxzoda Sanjar qizi (PEDAGOGS, 2024)
Abstract: In this paper, we can learn that what are conditional clauses, how to use them in what situations and how to use them to form correct sentences. It must be said that a thorough study of the subject of conditional clauses is very useful and beneficial for every English language learner.